Duodenum-preserving pancreatic head resection: 10-year follow-up of a randomized controlled trial comparing the Beger procedure with the Berne modification - Klaiber, Ulla; Alldinger, Ingo; Probst, Pascal; Bruckner, Thomas; Contin, Pietro; Köninger, Jörg; Hackert, Thilo; Büchler, Markus W.; Diener, Markus K. (Surgery, 2016)
Background - Since the introduction of the duodenum-preserving pancreatic head resection for operative treatment of chronic pancreatitis, various modifications of the original Beger procedure have emerged. A randomized controlled trial comparing the Beger procedure and the Berne modification indicated that the latter is an equivalent alternative, but a comparison of the long-term results of both procedures has not yet been published. - Methods - Between December 2002 and January 2005, 65 patients were randomized intraoperatively to the Beger or the Berne procedure. For this 10-year follow-up, patients were contacted by phone and in writing to evaluate patient-relevant outcome parameters. Statistical analysis was made on an intention-to-treat basis. - Results - Median follow-up was 129 (111-137) months. Forty of 65 patients were available for follow-up; 11 of the original study cohort had died, and 14 were otherwise lost to follow-up. Quality of life, pain, occupational disability, exocrine and endocrine pancreatic function, endoscopic interventions, and redo operations were comparable in both groups. More than half of the patients were completely free of pain, and the majority in both groups judged that the index operation had improved their quality of life. - Conclusion - Ten-year follow-up showed no differences in patient-relevant outcome parameters between the Beger and Berne procedures for treatment of chronic pancreatitis. Because short-term results have shown the Berne modification is superior in terms of operation time and duration of hospital stay, it should be preferred whenever possible, depending on the individual surgeon's expertise and the intraoperative findings.